1972
DOI: 10.1055/s-0028-1099043
|View full text |Cite
|
Sign up to set email alerts
|

Zur Problematik des akuten Mesenterialarterienverschlusses*

Abstract: Aufgrund der Angaben der Literatur und anhand von 32 eigenen Fällen von akutem Verschluß der A. mesenterica sup. wird die besondere Problematik dieser Erkrankung besprochen. Häufigste Ursache ist die Embolie, gefolgt von der akuten Thrombose. Die Symptomatik wird beschrieben, die Notwendigkeit der Frühdiagnose und der möglichst baldigen Behandlung wird betont. Nur die chirurgische Therapie ist

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1986
1986

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As a consequence of this mucosal injury, there may be a massive loss of plasma and fluid into the gut lumen (2) but also an increased passage of bacteria and other components from the gut lumen into the circulation (2). For instance, Fine (3) showed that ischaemia of the dog intestine increased the mucosal permeability to gut bacteria, and we recently found that ischaemia of the rat intestine causes an increased permeability to larger molecules such as dextran 3000 (T. Otamiri, R. Sjodahl, C. Tagesson.…”
Section: 1131-1136mentioning
confidence: 99%
“…As a consequence of this mucosal injury, there may be a massive loss of plasma and fluid into the gut lumen (2) but also an increased passage of bacteria and other components from the gut lumen into the circulation (2). For instance, Fine (3) showed that ischaemia of the dog intestine increased the mucosal permeability to gut bacteria, and we recently found that ischaemia of the rat intestine causes an increased permeability to larger molecules such as dextran 3000 (T. Otamiri, R. Sjodahl, C. Tagesson.…”
Section: 1131-1136mentioning
confidence: 99%